Conventional hearing aid amplification, notch therapy, or increased gain at tinnitus pitch : a randomised controlled multicentre study - Waechter, Sebastian; Timmer, Barbra H.B.; Olovsson, Maria; Pettersson, Petter; Frawley, Lorelei; Ibertsson, Tina; Thorén, Elisabet Sundewall; Jönsson, Anders (International Journal of Audiology, 2025)
Objective: To investigate whether modifying hearing aid gain at the individual’s tinnitus pitch augments tinnitus mitigation from hearing aid amplification. Design: Participants were randomised to receive hearing aids delivering either objectively verified Conventional Amplification (n = 36), Increased Gain at Tinnitus Pitch (n = 36), or eliminated gain at tinnitus pitch, so-called Notch Therapy (n = 36). Perceived tinnitus loudness, tinnitus distress, and symptoms of anxiety and depression, were examined at baseline (before hearing aid fitting), and after 3 and 12 months of hearing aid use, respectively. Forty-seven participants also underwent a speech recognition threshold test after 3 months hearing aid use. Study Sample: Adults experiencing chronic tinnitus for ≥3 months (n = 108). Results: Tinnitus distress decreased significantly in all groups after hearing aid fitting. No significant outcome measures differences between groups were found, except for speech intelligibility benefit with hearing aids. Greater speech intelligibility benefit was observed with conventional hearing aid amplification compared to Increased Gain at Tinnitus Pitch (p =.022) or Notch Therapy (p =.009). Conclusions: We recommend conventional, objectively verified, hearing aid amplification for tinnitus patients, as it has the ability to optimally simultaneously improve both tinnitus symptoms and speech intelligibility.
Keywords: Amplification; Hearing aids; Speech intelligibility; Tinnitus